Prevalence and molecular characterization of extended spectrum Beta-Lactamase producing multidrug-resistant Pseudomonas aeruginosa and Klebsiella pneumoniae isolates - Afsana, Sadia (2018)
This thesis report is submitted in partial fulfillment of the requirement for the degree of M.Sc in Biotechnology, 2017.